Low-Milliampere CT Fluoroscopy-Guided Percutaneous Drainage Placement after Pancreatic Surgery: Technical and Clinical Outcome in 133 Consecutive Patients during a 14-Year Period - Trumm, Christoph G.; Hackner, Danilo; Badmann, Katharina; Crispin, Alexander; Forbrig, Robert; Ozpeynirci, Yigit; Kuppinger, David; Pedersen, Vera; Liebig, Thomas; Stahl, Robert (Diagnostics, 2022)
(1) Purpose: To retrospectively assess the technical and clinical outcome of patients with symptomatic postoperative fluid collections after pancreatic surgery, treated with CT-guided drainage (CTD). (2) Methods: 133 eligible patients between 2004 and 2017 were included. We defined technical success as the sufficient drainage of the fluid collection(s) and the absence of peri-interventional complications (minor or major according to SIR criteria). Per definition, clinical success was characterized by normalization of specific blood parameters within 30 days after the intervention or a decrease by at least 50% without requiring additional surgical revision. C-reactive protein (CRP), Leukocytes, Interleukin-6, and Dose length product (DLP) for parts of the intervention were determined. (3) Results: 97.0% of 167 interventions were technically successful. Clinical success was achieved in 87.5% of CRP, in 78.4% of Leukocytes, and in 87.5% of Interleukin-6 assessments. The median of successful decrease was 6 days for CRP, 5 days for Leukocytes, and 2 days for Interleukin-6. No surgical revision was necessary in 93.2%. DLP was significantly lower in the second half of the observation period (total DLP: median 621.5 mGy*cm between 2011-2017 vs. median 944.5 mGy*cm between 2004-2010). (4) Conclusions: Technical success rate of CTD was very high and the clinical success rate was fair to good. Given an elderly and multimorbid patient cohort, CTD can have a temporizing effect in the postoperative period after pancreatic surgery. Reducing the radiation dose over time might reflect developments in CT technology and increased experience of interventional radiologists.
CRIS-Team WoS Importer:2022-09-30